Analysis of the Relationship Between Factors of the Health Belief Model (Perceived Benefit and Perceived Barrier) and Service Quality (Reliability and Responsiveness) on Outpatient Satisfaction, Controlling for Sociodemographic Characteristics, at the Cardiology Clinic of Hospital X in Indonesia - Lesmana, Michael Aditya; Lis Indrianto , Agoes Tinus (Journal Research of Social Science, Economics, and Management, 2026)
Patient satisfaction is a critical measure of healthcare quality, particularly in cardiac outpatient services where cardiovascular disease constitutes a major global health burden. In Indonesia, stroke and ischemic heart disease represent the leading causes of mortality, emphasizing the need for effective and responsive cardiac care. Despite a national hospital satisfaction rate of 82.7%, this figure remains below the government target of 90–95%, highlighting gaps in service delivery, especially in responsiveness and reliability. This study aims to examine the influence of Health Belief Model dimensions (perceived benefits and perceived barriers) and SERVQUAL service quality attributes (reliability and responsiveness) on outpatient satisfaction at a cardiac polyclinic, while controlling for sociodemographic factors such as age, gender, education, and marital status. A quantitative cross-sectional design was employed, collecting data from 146 adult patients using structured questionnaires. Data were analyzed through hierarchical multiple regression to determine the partial and combined effects of the independent variables. The findings indicate that responsiveness is the most dominant predictor of patient satisfaction, followed by reliability and perceived barriers, whereas perceived benefits and sociodemographic factors showed no significant influence. These results suggest that operational efficiency and barrier mitigation are more impactful than inherent medical benefits in determining patient satisfaction. The study concludes that prioritizing responsiveness, reliability, and the reduction of procedural barriers can substantially improve patient satisfaction, providing actionable insights for healthcare management and policy optimization.